Zepha the monster squid - Blade, Adam.; Tucker, Ezra N. (New York : Scholastic, 2008)
Desperate for knowledge about his mysterious father and determined to finish his quest, Tom heads west, where Cepha the Giant Squid threatens the seas. But his arrival brings back memories of his encounter with Sepron the Sea Serpent, an encounter he barely had survived.
RL3.
007-010.
Keywords: Adventure stories; Squids -- Fiction; Monsters -- Fiction; Fantasy